Journal Clubs: What Works for the Bachelor Student? - Fylking, Cecilia Black; Opheim, Elin (Septentrio Conference Series, 2020)
Journal clubs are closely interlinked with evidence based practice. At Faculty of Social and Health Sciences at Inland Norway University of Applied Sciences our students are required to write literature reviews for their bachelor degree, and there is an increasing need for guiding the students into academic methodology through critically assessing research articles. The purposes of starting journal clubs at our faculty is to guide the students into the academic genre, to help them gain confidence in reading research articles, and to broaden the perspective between theory and practice. Better semester grade is a secondary goal to our aim as it probably is hard to operationalize. We wish to establish a cooperation with the faculty staff, especially the ones involved in teaching evidence based practice. Wilson & Deighton (2016) describes that students find it difficult to approach research articles, and that journal clubs are suitable and an activating manner to introduce the students to the academic genre. Deenadayalan et al. (2008) comments that using case studies as a basis for academic discussion, fills the gap between theory and practical approach to the subject. There are several elements to pay attention to if the journal clubs are to become a success, and Deenadayalan et al. (2008) emphasizes among other things a clear purpose for the students' involvement, as well as leadership, insentives and preparedness. In our project dating, we wish to discuss the possibility to do pilots for nursing students either in the last semesters of their courses, or with master students. We are interested in previous experiences with nursing students, and we want to look into which factors that makes the clubs function and how our aim might be reached.